Nanocrystalline based Mitigation Technique for Very Fast Transient over Voltages in Gas Insulated Substations - et. al., R.Durga Rao, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
: in gas insulated substations, issue of very fast transient over voltages is very familiar problem because of its effects on live ultra-high voltage equipment. During switching events of disconnectors and circuit breakers prestrikes and restrikes occur due to which voltage transients propagate through gas insulated switchgear. Reflection retraction of these transients increases voltage magnitude and generates very high frequency oscillations. Mitigation or suppression of these voltage transients is important to protect equipment and their dielectric strength and insulation. Due to very high frequency stress, they wield on the apparatus and their magnitude (up to 3.5pu), they create an important problem in the design of ultra-high voltage Gas Insulated Substations. In this paper nanocrystalline based mitigation technique for VFTOs is presented. Nanocrystalline rings can be placed around inner conductor of GIS switchgear. This method of mitigation technique is investigated with four ultra-high voltage substations simulation test setup. Simulation results are presented in MATLAB/SIMULINK